White Extremism: Psychological Perspectives - Zora Arfina Sukabdi (Asosiasi Psikologi Forensik (Apsifor), 2025)
Whiteness is a fluid concept as the definition of “white” continues to change throughout history. In terms of social and political construction, whiteness is similar to the construction of race. The term “white”, although it was initially inspired by ‘being white’, does not simply refer to a person's skin color; but rather an ideology based on their views, values, behavior, habits and attitudes. This ideology leads to an unequal distribution of power and privilege. Implementing literature review, this article investigates the origins of the abbreviated